Preceding Subculture Conditions Affect Growth Characteristics of Beer Spoilage Lactic Acid Bacteria in Quality Control Culture Media: Comparative Study on Hard-to-Culture and Culturable Secundilactobacillus (Lactobacillus) paracollinoides Strains. (2nd October 2021) - Shimokawa, Masaki; Suzuki, Koji
Abstract: Beer spoilage lactic acid bacteria (LAB) often display hard-to-culture characteristics and fail to grow on conventional quality control (QC) laboratory media, while retaining growth capability in beer. This phenomenon is at least partly due to profound adaptation of spoilage LAB to the brewing environments, where multifactorial antibacterial hurdles and low temperature stress are encountered. In this study, changeable culturability of Secundilactobacillus ( Lactobacillus ) paracollinoides strains, JCM 11969 T and JCM 15729, has been evaluated by comparing the variants obtained under various preceding subculture conditions. Sodium acetate substantially inhibited the growth of hard-to-culture S. paracollinoides variants, with smaller negative impacts for growth observed with yeast extract, peptone, and manganese sulfate. Growth inhibition was also observed at values higher than pH5.3 for hard-to-culture JCM 11969 T variants and higher than pH5.0 for hard-to-culture JCM 15729 variants, respectively. In contrast, culturable S. paracollinoides variants exhibited sensitivities to low pH and grew well at pH 5.6 or even higher. Strikingly, the addition of sodium acetate led to increased colony forming units for culturable JCM 15729 strains, suggesting that sodium acetate exerts both positive and negative effects on the growth of S. paracollinoides strains. It has been also demonstrated that hard-to-culture and culturable states are reversible for S. paracollinoides JCM 11969 T and JCM 15729, depending on the preceding subculture conditions. Taken together, it has been suggested that culturability of S. paracollinoides strains is easily changeable, and brewing microbiologists must ensure their culturability is maintained as observed upon primary isolation.